2009
DOI: 10.1002/ffj.1934
|View full text |Cite
|
Sign up to set email alerts
|

Influence of carbonation on aroma release from liquid systems using an artificial throat and a proton transfer reaction–mass spectrometric technique (PTR–MS)

Abstract: To determine whether carbonation affects aroma release from liquid systems, carbonated and non-carbonated flavoured model systems were prepared and volatile release was determined under static (equilibrium) and dynamic conditions. A model flavour system was added as a single compound or as a mixture of the six aroma compounds used in this study. Volatile release under dynamic conditions involved using a home-made device simulating an artificial throat, coupled to a proton transfer mass spectrometer (PTR-MS). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 20 publications
1
25
0
Order By: Relevance
“…Limited previous research into the physiochemical effects of carbonation on static volatile partitioning has reported inconclusive results. Saint-Eve et al 16 reported an increase in headspace volatile partitioning into the gas phase due to carbonation, while another study found decreases 6 and one found the effects to be compound specific 15 . This variation may be due to differences in methodology.…”
Section: Headspace Sampling -Staticmentioning
confidence: 98%
See 3 more Smart Citations
“…Limited previous research into the physiochemical effects of carbonation on static volatile partitioning has reported inconclusive results. Saint-Eve et al 16 reported an increase in headspace volatile partitioning into the gas phase due to carbonation, while another study found decreases 6 and one found the effects to be compound specific 15 . This variation may be due to differences in methodology.…”
Section: Headspace Sampling -Staticmentioning
confidence: 98%
“…However, in-vitro methods showed the opposite effect to those seen in-vivo. Recent experiments by Pozo-Bayon et al 15 using a model mouth found some compounds increased partitioning into the gas phase, while some decreased due to carbonation. These results represent in-vitro modelling and could be different to actual in-vivo behaviour both in magnitude as well as in direction.…”
Section: In-vivo Samplingmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the impact of CO 2 and oxygen at disgorging on the concentrations of the VOCs studied is not known, yet both are likely to affect VOC concentrations as rising and collapsing bubbles act as continuous "portals" for volatile aromas in Champagne wine [34]. Additionally, carbonation has been reported to increase extremely volatile compounds i.e., ethyl butanoate, but not impact less volatile compounds, e.g., isoamyl acetate, due to a specific effect that is dependent on the physiochemical characteristics of each compound [35].…”
Section: Odour Thresholds In Sparkling Winesmentioning
confidence: 99%